Performance: A critical introduction - Carlson, Marvin (London Routledge, 2004)
his comprehensively revised, illustrated edition discusses recent performance work and takes into consideration changes that have taken place since the book's original publication in 1996. Marvin Carlson guides the reader through the contested definition of performance as a theatrical activity and the myriad ways in which performance has been interpreted by ethnographers, anthropologists, linguists, and cultural theorists. Topics covered include: *the evolution of performance art since the 1960s*the relationship between performance, postmodernism, the politics of identity, and current cultural studies*the recent theoretical developments in the study of performance in the fields of anthropology, psychoanalysis, linguistics, and technology.With a fully updated bibliography and additional glossary of terms, students of performance studies, visual and performing arts or theatre history will welcome this new version of a classic text.